DESIMINASI TEKNOLOGI PEMANFAATAN LIMBAH UNTUK PENGEMBANGAN USAHA PETERNAKAN KOMPETITIF DAN BERKELANJUTAN DI DESA BANJARANGKAN - Mudita, I. M.; Kayana, I. G. N; Siti, N. W.; Wirawan, I. W; Partama, I. B. G. (Buletin Udayana Mengabdi; Vol 13 No 2 (2014): Vol 13, No. 2 (2014))
The knowledge and technology for community service was carried out at Bali Cattle Group Farmers Dharma Kerti Sedana (as partner I) and Winangun Kertih (as partner II) on Banjarangkan Village, Klungkung Regency. It is aimed to optimise use waste resources on bali cattle production development. Technolgy production of bio-innocullant based on rumen liquor waste Bali-bioand utilization on produce feed ration silage based on waste, produce organic fertilizerand biourine was desimination for all partners with socialization, short training and demonstration project activities.Result of activities showed participant partner on all activities are high. The socialization and short training was followed by 73,08% members of partners I and 70% members of partners II, 30,77% partner I and 35% partner II to propose their problem on Bali cattle production, and 50% partners I and 55% partners II participate on short course activity. Eventhough participant partner on activities of demonstration projects showed 80,77% partners I and 90% partners II participate on produce of feed silage, organic fertilizer and biourine with IbM worker team, 73,08% partners I and 75% partners II can produce its products by itself. It was concluded that activity of desimination of technology at partners can continously done better which showed high level of participation and adoption of technology transfer. Keywords: Bali-bio, biourine, feed silage, organic fertilizer, and group farmers